2018
DOI: 10.3126/nmj.v1i2.21591
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Evaluation of Skin Neoplasms

Abstract: Introduction: Skin tumor incidence has increased over the last several decades. A wide range of tumors are encountered in clinical practice. Accurate identification of skin lesions is vital in ensuring malignancies are not missed and that they are treated early to avoid morbidity and mortality.Materials and Methods: A retrospective cross sectional hospital based study on a series of cases was performed in the Department of Pathology, Patan Academy of Health Sciences, Patan Hospital, Lalitpur, Nepal from April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 5 publications
3
6
4
Order By: Relevance
“…Females also had more benign tumors in various other studies from Nepal. [10][11][12] Similar to our study malignant skin tumors were commoner in females in a study by Adhikari et al 19 This may be due to the fact that females have health seeking behavior for their skin problems as they are more cosmetically concerned compared to males.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Females also had more benign tumors in various other studies from Nepal. [10][11][12] Similar to our study malignant skin tumors were commoner in females in a study by Adhikari et al 19 This may be due to the fact that females have health seeking behavior for their skin problems as they are more cosmetically concerned compared to males.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were observed in various studies. 10,[11][12] In our study, out of 105 benign tumors, soft tissue tumors of dermis (37.1%) were commonest followed by keratinocytic tumors. Karki et al also showed out of 142 cases of benign tumors, soft tissue tumors of the dermis (34%) were commonest followed by keratinocytic tumors.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations